Features of the organization of customs control after release of goods - O. A. Dmitrieva; S. S. Ilyukhina (Путеводитель предпринимателя, 2020)
This article provides the question of organization continuous customs control before and after the release ofgoods, analysis of risk-categorization system of foreign trade activities participants and conditions for transfer the focus ofcustoms control on the stage after the release of goods.